2017
DOI: 10.21037/jovs.2017.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical video-assisted thoracoscopic surgery segmentectomies based on the three-dimensional reformation images

Abstract: Segmentectomy was first done in 1939 by Churchill and Belsey in 1939. Video-assisted thoracoscopic surgery (VATS) segmentectomies are still more technically challenging than VATS lobectomies. With the increasing rate of early stage lung carcinomas, the thoracoscopic segmentectomies may have a major role in a near future. Four anatomical VATS segmentectomy videos clips were shared in this study. CT three-dimensional reformation could exactly show the small pulmonary nodule's precise position, clarifies the surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Studies have indicated that the 3D images can be rotated freely and visualized interactively from any angle, which can directly measure the distance and positional relationship between the blood vessels, bronchus and the lesion, perform intraoperative navigation with the assistance of related software, 33 avoid the unnecessary dissection of lung tissue, and save intraoperative time to find and discern the segmental pulmonary venous vessels, thus shortening the operation time, 34 reducing the amount of bleeding during the operation, and improving the success rate of the operation. Three‐dimensional reconstruction is helpful for preoperative positioning, surgical planning, preoperative simulation and intraoperative navigation, and provides a reference for formulating an individualized surgical plan 35–37 …”
Section: Advantages Of Three‐dimensional Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that the 3D images can be rotated freely and visualized interactively from any angle, which can directly measure the distance and positional relationship between the blood vessels, bronchus and the lesion, perform intraoperative navigation with the assistance of related software, 33 avoid the unnecessary dissection of lung tissue, and save intraoperative time to find and discern the segmental pulmonary venous vessels, thus shortening the operation time, 34 reducing the amount of bleeding during the operation, and improving the success rate of the operation. Three‐dimensional reconstruction is helpful for preoperative positioning, surgical planning, preoperative simulation and intraoperative navigation, and provides a reference for formulating an individualized surgical plan 35–37 …”
Section: Advantages Of Three‐dimensional Reconstructionmentioning
confidence: 99%
“…Three‐dimensional reconstruction is helpful for preoperative positioning, surgical planning, preoperative simulation and intraoperative navigation, and provides a reference for formulating an individualized surgical plan. 35 , 36 , 37 …”
Section: Advantages Of Three‐dimensional Reconstructionmentioning
confidence: 99%
“…The application of segmentectomy, which is associated with less trauma, fewer complications, and less pain for patients than thin-section and low-dose computed tomography, is more conducive for patients with non-small-cell lung cancer ( 3 ). 3D computed tomography of lung segments can ensure the position of the lung tumor within the anatomical segment and assist in the prediction of surgical margins ( 4 ). However, whether preoperative 3D lung simulation is better than non-3D procedures in segmentectomy for lung cancer remains controversial.…”
Section: Introductionmentioning
confidence: 99%